Numerical Studies of Propeller Exciting Bearing Forces under Nonuniform Ship’s Nominal Wake and the Influence of Cross Flows - Huilan Yao; Huaixin Zhang (Shock and Vibration, 2017)
Propeller exciting forces are the main causes of stern vibrations. In this paper, three-dimension exciting bearing forces of one blade and the whole propeller under nonuniform ship’s wake were predicted, and the influence of cross flows on these exciting forces was studied. All simulations were carried out using a commercial solver, STAR-CCM+. To obtain the nominal wake for studying propeller exciting forces, flow field around a bare hull was simulated. Numerical results were widely validated by measured data, especially the velocity field at the propeller plane. Harmonic characteristics of the nonuniform ship’s wake were studied. Then, a propeller under uniform inflow and nonuniform ship’s wake with/without cross flows was simulated. Free-water surface and hull boundary were considered using a specially designed dummy stern. Results show that the influence of cross flows on propeller exciting forces is obvious. As for the exciting forces of one blade, the cross flows have greater influence on the axial force. As for the exciting forces of the whole propeller, the cross flows have greater influence on the transverse and vertical forces, and if the cross flows in ship’s wake are not considered, the amplitudes of the main harmonics of transverse and vertical forces increase obviously.